Pengaruh Tata Kelola Perusahaan dan Manajemen Laba terhadap Nilai Emiten melalui Profitabilitas Perusahaan - Miranda Nuraini; Honesty Sinurat; Afriosa Syawitri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Firm value reflects investors’ assessment of a company’s performance and future prospects, making it an important indicator in the capital market. In the food and beverage sector, firm value is influenced by various internal factors, including the implementation of Good Corporate Governance (GCG), earnings management practices, and profitability. Previous studies examining the relationships among these variables have produced inconsistent findings, creating a need for further investigation. This research examines the influence of Good Corporate Governance and earnings management on firm value through profitability as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach using secondary data obtained from annual financial reports. A purposive sampling technique was applied, resulting in 30 companies with 150 observations. Data were analyzed using multiple linear regression and path analysis. The findings indicate that Good Corporate Governance and earnings management do not significantly affect profitability. Good Corporate Governance has a significant effect on firm value, while earnings management does not significantly influence firm value. Profitability demonstrates a positive and significant effect on firm value. Furthermore, profitability is unable to mediate the relationship between Good Corporate Governance and firm value but is able to mediate the relationship between earnings management and firm value. These findings highlight the importance of profitability as a determinant of firm value and provide implications for investors in evaluating corporate performance.